Harmony of Revelation and Innovation: the Quran's insight into contemporary scientific breakthroughs - Muhsin, Sayyed Mohamed (2023)
This paper explores the foundational principles of Islamic philosophy in knowledge acquisition, science, and technology. It emphasizes the integration of knowledge and faith, aligning research with community interests, and the ethical responsibility in the use of modern science and technology. Rooted in the five higher objectives of maqāṣid al-sharīʿah, the Islamic ethical framework proves crucial for addressing contemporary challenges and achieving sustainable development goals. The abstract underscores the dual nature of modern science and technology, highlighting the necessity of a well-grounded ethical framework for responsible applications. It also discusses the ethical facets of modern biotechnology, encompassing human relationships with God, interactions among humans, and the treatment of other beings. The abstract concludes by acknowledging broader concerns surrounding biotechnology and emphasizes the overarching principle that science and technology should serve the betterment of humanity.